Business vocabulary in use : Cambridge Professional English. - Mascull, Bill, ....- (Cambridge : University Press, 2005)
Business Vocabulary in Use is a new addition to the best-selling English Vocabulary in Use range. Primarily designed as a self-study reference and practice book, it can also be used for classroom work. The book covers a huge range of business topics including: jobs; people and organisations; production; marketing; finance and the economy, and business culture. Learners will develop essential business communication skills, focusing on the language used for meetings, negotiations and presentations. Key Features 66 easy-to-use units: vocabulary items are presented and explained on left-hand pages with a range of practice exercises on right-hand pages. Presents and explains new words in context and shows learners how to use them. Contains a comprehensive, learner-friendly answer key. Colour illustrations and photographs.
Keywords: Zakelijke communicatie -- Engels